2013
DOI: 10.1016/j.humimm.2012.12.017
|View full text |Cite
|
Sign up to set email alerts
|

The autoimmune-predisposing variant of lymphoid tyrosine phosphatase favors T helper 1 responses

Abstract: The C1858T single nucleotide polymorphism in PTPN22, which is the gene encoding lymphoid tyrosine phosphatase (LYP), confers increased risk for various autoimmune disorders in Caucasians. Although the disease-associated LYP allele (LYP*W620) is a gain-of-function variant that has higher catalytic activity than the major allele (LYP*R620), it is still unclear how LYP*W620 predisposes for autoimmunity. Here, we compared both T cell signaling and T cell function in healthy human donors homozygous for either LYP*R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 27 publications
(51 reference statements)
1
65
0
Order By: Relevance
“…We hypothesize that, despite the increased susceptibility to autoimmunity caused by PTPN22 R620W in humans, the resistance conferred by this allele to both bacterial and viral infections may have resulted in a selective advantage. Furthermore healthy carriers of the PTPN22 R620W variant have exaggerated Th1 responses with increased IFNγ, TNFα, and IL-2 production, similar to the data presented in this report (55). It will be interesting to extend this genotypic analysis to other infectious diseases in the future.…”
Section: Ptpn22 Deficiency Prevents Exhaustion Of Viral-specific Cd8 supporting
confidence: 84%
“…We hypothesize that, despite the increased susceptibility to autoimmunity caused by PTPN22 R620W in humans, the resistance conferred by this allele to both bacterial and viral infections may have resulted in a selective advantage. Furthermore healthy carriers of the PTPN22 R620W variant have exaggerated Th1 responses with increased IFNγ, TNFα, and IL-2 production, similar to the data presented in this report (55). It will be interesting to extend this genotypic analysis to other infectious diseases in the future.…”
Section: Ptpn22 Deficiency Prevents Exhaustion Of Viral-specific Cd8 supporting
confidence: 84%
“…These findings are mirrored in T1D-suggesting common mechanisms, that may initially be driven by hyper-responsiveness, that the T cells compensated for with time, but which ultimately results in an expanded memory compartment. In addition to the expanded CD4 T cell memory compartment seen in in healthy subjects who carry the PTPN22 risk variant [55], Vang et al reported increased production of IFNγ, and decreased production of IL-17, in PMA/ionomycin-stimulated CD4 + memory T cells from healthy individuals homozygous for the risk variant (T/T) that paralleled enhanced activation of AKT [56]. These findings implied altered lineage commitment within Lyp620W-expressing CD4 + T cells.…”
Section: Genetic Variants Associated With T1d Indicate a Genetic Basimentioning
confidence: 99%
“…There is evidence that each of these pathways may be altered in T1D: 1) A skewing of T cell toward Th17 and Th1 lineages is described (see above), 2) IL-6 levels are increased in T1D[83], a variant in the IL-6R gene is associated with T1D further implicating this pathway, and ongoing studies indicate that the IL-6 signaling pathway may be enhanced in T1D (unpublished observations JHB) and 3) Genetic risk variants including PTPN22 impact the PKB/c-AKT pathway and may contribute to Teff resistance. In this respect the PTPN22 risk variant associated with T1D could play a role as it has been shown to lead to enhance phophsphorylation of AKT [56], (unpublished JHB). Defining the mechanisms through which effector T cells evade Treg in T1D will allow directed therapies to reinstate tolerance.…”
Section: Response To Regulation Is Altered In T1d-effector Cells Are mentioning
confidence: 99%
“…Resolution of chronic HBV infection is associated with robust and sustained T-cell responses to the virus. A recent study demonstrated that the autoimmune-predisposing variant of PTPN22 1858C/T polymorphism favors T helper 1 responses[32]. Further, a previous study showed that the strength of association between the rheumatoid arthritis and the PTPN22 -1123G/C polymorphism is analogous to that observed for 1858C/T polymorphism[31].…”
mentioning
confidence: 88%